Sevoflurane inhibited reproductive function in male mice by reducing oxidative phosphorylation through inducing iron deficiency - Zhang, Xue; Zuo, Yong; Zhang, Jianhua; Zhang, Di; Naeem, Muhammad; Chang, Yanzhong; Shi, Zhenhua (Frontiers in Cell and Developmental Biology, 2023)
Sevoflurane (Sev) is one of the commonly used inhalation anesthetic chemicals in clinics. It has great impact on spermatogenesis and fertilization in male animals. The underlying mechanism remains largely unexplored. Based on our previous research, we hypothesized that Sev induced iron metabolism disturbance in the testis and epididymis and inhibited the spermatogenesis. In this study, two-month-old C57BL/6 male mice were treated with 3% Sev for 6 h, and their fertility (including sperm concentration, sperm mobility, and the number of offspring) was evaluated. Mice testis, epididymis, and sperm were harvested and subjected to Western blot analysis and immunofluorescence analysis. Iron levels were reflected by the gene expression of iron metabolism-related proteins (including ferritin, TfR1, and FpN1) and ICP-MS and Perl’s iron staining. Electron transport and oxidative phosphorylation levels were measured by Oxygraph-2k and ATP contents. The activity of ribonucleotide reductase was evaluated by assay kit. DNA synthesis status in testis and/or epididymis was marked with BrdU. Cell proliferation was evaluated by double immunofluorescence staining of specific protein marker expression. Our results revealed that the mice exposed to Sev showed damaged testicular and epididymis structure and significantly reduced the sperm concentration, sperm motility, and fertility. Sev decreases the iron levels through down-regulating the expression of H-ferritin, L-ferritin, and FpN1, and up-regulating the expression of TfR1 in the testis and epididymis. Iron levels also significantly reduced in germ cells which decrease the number of germ cells, including sperm, Sertoli cells, and primary spermatocyte. Iron deficiency not only decreases electron transport, oxidative phosphorylation level, and ATP production but also suppresses the activity of ribonucleotide reductase and the expression of Ki67, DDX4, GATA1, and SCP3, indicating that Sev affects the spermatogenesis and development. Meanwhile, Sev impaired the blood-testis barrier by decreasing the ZO1 expression in the testis and epididymis. The damage effect induced by Sev can be significantly ameliorated by iron supplementation. In conclusion, our study illustrates a new mechanism by which Sev inhibits spermatogenesis and fertility through an oxidative phosphorylation pathway due to iron deficiency of epididymis and testis or sperm. Furthermore, the damaging effects could be ameliorated by iron supplementation.